Próba przezwyciężenia doktryny podwójnej prawdy przez Galileusza - Sołtysiak, Marek (Humaniora. Czasopismo Internetowe, 2019)
The article is an attempt to answer the question of whether Galileo has overcome the doctrine of double truth in Copernican letters. The answer to this question is not unequivocal, just as the ‘Galileo case’ is unequivocal. As it is well known, the attempt to defend Copernicanism ended tragically for him. He had to revoke his view that the Earth revolves around the Sun. Also, as for the „evidence” presented by him on this matter, it proved to be either insufficient or false. However, the principle of the autonomy of science and faith, his emphasis on the authority of scientific knowledge and the authority of the Bible survived the period of condemnation of his thoughts and made itself felt in the nineteenth century, and today they determine the fides et ratio relation.